Evaluasi Program Boarding School dalam Upaya Meningkatkan Mutu Lulusan di MAN 1 Gunungkidul - Jauhari Iswahyudi (Jurnal Pendidikan Madrasah, 2020)
This research aims to obtain empirical descriptions and evaluate the implementation of boarding school program at MAN 1 Gunungkidul. This research is an evaluation study that uses a qualitative approach. The evaluation model used is a formative evaluation model developed by Scriven. In this study, evaluation criteria were set before data collection, which was developed through library review and based on the guidelines for organizing boarding school program compiled by the Management Team of Boarding School MAN 1 Gunungkidul. The data analysis techniques used are qualitative analysis techniques according to Miles and Huberman that include four main activities, namely: data collection, data presentation, data reduction and conclusion drawing. The results showed: (1) The selection system of boarding school program participants is carried out objectively and transparently using the procedures specified by madrasa, (2) Funding for boarding school program is largely the responsibility of the committee and zakat funds, only a small portion of which is a burden on parents of the parents of the student guardians, (3) Dormitory facilities are still not ideal, need to be built adequate dormitories to maintain the boarding school program, and (4) The learning achievement of boarding school students in both academic, religious and non-academic fields is still lacking.